The use of low alkalinity MgO-SiO₂ formulation to encapsulate bacteria for self-healing concrete - Xiao, Xi (2023)
Concrete structures are inherently brittle, rendering them susceptible to cracking, which in turn allows moisture, carbon dioxide, and harmful ions to penetrate, ultimately resulting in a loss of durability and strength. Incorporating encapsulated or immobilized bacteria in concrete has proven to be an effective way to promote the self-healing of cracks. However, the commonly used bacteria-based capsules and carriers tend to significantly reduce the matrix strength. To address the strength reduction while facilitating self-healing, the present study proposes utilizing the MgO-SiO2 formulation, a low alkalinity cementitious system, for encapsulating bacteria in self-healing concrete. Results showed that the incorporation of the capsule can maintain the strength of a cement paste. Furthermore, the addition of the capsule to the PC paste can engage effective self-healing. Cracks between 250 and 350 µm can reach 97% closure while cracks between 350 and 600 µm can reach 85% of closure, and the water passing through the crack reduced around 80% after 40 wet/dry conditioning cycles. Besides, the capsule possessed long-term stability where the concentration of viable bacteria remained stable in the capsule.